Intercropping Lentil with Mukhikachu (Collocasia Esculenta) at Different Planting Systems (Bangladesh Journal of Agricultural Research, 2012)
The experiment was conducted at the Regional Agricultural Research Station,  BARI, Jessore during consecutive two years (2007-08 and 2008-09) to find out  the comparative performance of different intercropped lentil with Mukhikachu  for getting higher yield and economic return. Five treatments comprised of T1=  Sole lentil (30 cm apart continuous seeding), T2 = Sole mukhikachu [(double  row) = 20 cm/55/20 cm x 45 cm], T3= Mukhikachu (double row) + 1 row of  lentil 30 cm apart (33% seeding ratio) between 2 double row of mukhikachu, T4 = Mukhikachu (double row) + 2 rows of lentil 30 cm apart (66%) between 2  double row of mukhikachu and T5= Mukhikachu (double row) + lentil broadcast  (100%). Intercropping systems did not affect the rhizome yield of mukhikachu  significantly but affected the seed yield of lentil. Lentil and mukhikachu  equivalent yield were the highest (5.87 in 2007-08 and 6.09 t/ha in 2008-09, and  27.24 in 2007-08 and 30.45 t/ha in 2008-09, respectively) in treatment T4. This  treatment also gave the highest LER (1.63 in 2007-08 and 1.54 in 2008-09), net  return (Tk. 290508 in 2007-08 and Tk. 368900/ha in 2008-09) with BCR of 4.19  in 2007-08 and 4.88 in 2008-09, respectively. It reveals that lentil could be  grown easily in double row system of Mukhikachu without hampering yield of  Mukhikachu with higher benefit and also enhanced lentil production in the area.   DOI: http://dx.doi.org/10.3329/bjar.v36i4.11757   Bangladesh J. Agril. Res. 36(4): 669-676, December 2011